Coenzyme Q10 supplementation modulates NF?B and Nrf2 pathways in exer-cise training - Pala, Ragıp; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Ali, Shakir; Çınar, Vedat; Atalay, Mustafa; Şahin, Kazım (My University, 2016)
This study reports the effects of Q10, coenzyme Q10 or ubiqui-none, a component of the electron transport chain in mitochon-dria, on nuclear factor kappa-light-chain-enhancer of activated B cells (NF?B), inhibitors of kappa B (I?B), nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and hemeoxygenase 1 (HO-1) in rats after chronic exercise training for 6 weeks. 8-week old male Wistar rats were assigned randomly to one of four treat-ments planned in a 2 x 2 factorial arrangement of two condition (sedentary vs. exercise training), and two coenzyme Q10 levels (0 and 300 mg/kg per day for 6 weeks). The expression levels of the target proteins were determined in the heart, liver and mus-cle, and biochemical parameters including creatinine, urea, glucose and lipid profile were investigated in plasma. When compared with sedentary group, significant decreases in heart, liver and muscle NF?B levels by 45%, 26% and 44% were observed in Q10 supplemented rats after exercise training, re-spectively, while the inhibitory protein I?B increased by 179%, 111% and 127% in heart, liver and muscle tissues. Q10 supple-mentation caused an increase in Nrf2 (167%, 165% and 90%) and HO-1 (107%, 156% and 114%) after exercise training in heart, liver and muscle tissues (p < 0.05). No significant change was observed in any of the parameters associated with protein, carbohydrate and lipid metabolism, except that exercise caused a decrease in plasma triglyceride, which was further decreased by Q10. In conclusion, these results suggest that Q10 modulates the expression of NF?B, I?B, Nrf2 and HO-1 in exercise training, indicating an anti-inflammatory effect of Q10 and emphasizes its role in antioxidant defense.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Coenzyme Q10; Exercise; Signaling pathway